Peranan Tiktok Dalam Membangun Sikap Asertif Para Kreator Konten Penyandang Disabilitas - wiwi isnaini (Aliansi Desainer Produk Industri Indonesia (ADPII), 2023)
During 20 years of metamorphosis, social media has become a place for anyone to be creative, express and shape images and increase income in the digital world. Disability or Different Ability is a term aimed at someone who experiences limitations, both physically, intellectually, mentally, or sensory for a long time so that they have difficulty carrying out activities and participating fully and effectively with other citizens so that this becomes a cause low self-confidence in his abilities to perform in society. The presence of Tiktok is a new phenomenon because, Tiktok is felt as a home for more people, including people with disabilities, to be more open compared to other social media. Through this research, we will explore why tiktok is more inclusive and how, with its various features and uniqueness, it can make people with disabilities more assertive and open to their differences and able to create educational and informational content that gradually erode bad perceptions about their various disabilities. Key Words : Disabilities, Assertive, Tiktok